Oral midazolam reduces cortisol levels during local anaesthesia in children: a randomised controlled trial - Heloisa Sousa GOMES; Patrícia CORRÊA-FARIA; Tarcília Aparecida SILVA; Saul Martins PAIVA; Paulo Sérgio Sucasas COSTA; Aline Carvalho BATISTA; Luciane Rezende COSTA (Sociedade Brasileira de Pesquisa Odontológica, 2015)
Little is known about whether midazolam sedation can reduce salivary cortisol levels and consequently influence children's behaviour during dental treatment. The aim of this study was to evaluate the effect of midazolam sedation on salivary cortisol and its correlation with children's behaviour during restorative dental treatment. Eighteen healthy children, aged two to five years, were randomly assigned to two dental treatment appointments, both with physical restraint: oral midazolam 1 mg/kg (MS) and placebo (PS). An observer assessed the children's behaviour (videos) using the Ohio State University Behavioral Rating Scale (OSUBRS). The children's saliva was collected just after waking up, on arrival at the dental school, 25 minutes after local anaesthesia, and 25 minutes after the end of the procedure. Salivary cortisol levels were determined using the enzyme-linked immunoabsorbent assay. The data were analysed by bivariate tests and multivariate analysis of variance (5% level). Salivary cortisol levels were lower in the MS group than in the PS group at the time of anaesthesia (p = 0.004), but did not vary during the appointment within sedation (p = 0.319) or placebo (p = 0.080) groups. Children's behaviour was negative most of the time and did not differ between MS and PS; however, the behaviour (OSUBRS) did not correlate with salivary cortisol levels. Oral midazolam is able to control salivary cortisol levels during dental treatment of pre-schoolers, which might not lead to better clinical behaviour.